Ten little Indians : stories - Alexie, Sherman, 1966- (Grove Press, 2003)
In Alexie<U+2019>s first story, “The Search Engine,” Corliss is a rugged and resourceful student who finds in books the magic she was denied while growing up poor. In “The Life and Times of Estelle Walks Above,” an intellectual feminist Spokane Indian woman saves the lives of dozens of white women all around her to the bewilderment of her only child. “What You Pawn I Will Redeem” starts off with a homeless man recognizing in a pawn shop window the fancy-dance regalia that was stolen fifty years earlier from his late grandmother.